The Future of European Security
XIV, 216 p.
Keywords: Brings together a number of prominent American and European policy-makers and analysts to examine the key issues involved in the "new political thinking" about Europe's security. The overall picture is optimistic, but events such as the Yugoslav civil war suggest perhaps a more dangerous future.